2017
DOI: 10.18203/2349-2902.isj20163973
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum albumin and body mass index as predictors of post-operative morbidity and mortality in elective major abdominal surgeries

Abstract: INTRODUCTIONThe adverse effects of malnutrition on the morbidity and mortality of patients was first recognized by Hippocrates (460 BC-370 BC) many centuries ago. It is common and occurs in about 30% of surgical patients with gastrointestinal diseases and in up to 60%of those in whom hospital stay has been prolonged because of postoperative complications. There is a substantial evidence to show that patients who have signs of malnutrition have a higher risk of complications and an increased risk of death in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
(6 reference statements)
1
10
0
Order By: Relevance
“…Patients with low albumin had more number of complications as compared to patients with normal complications. This study is concordant with the study conducted by Bhagvat VN et al 9 Out of the various complications, wound infection was the most common complication. 26% patient had wound infection because of low albumin.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with low albumin had more number of complications as compared to patients with normal complications. This study is concordant with the study conducted by Bhagvat VN et al 9 Out of the various complications, wound infection was the most common complication. 26% patient had wound infection because of low albumin.…”
Section: Discussionsupporting
confidence: 92%
“…The mean age group in this study group is 45.7 years. The highest percentage of patients were in the age group 41-50 years comprising of 27% compared to study conducted by Vikrant M Bhagavat et al [6] on role of serum albumin and BMI as predictors of post operative morbidity and mortality in major abdominal surgeries where the highest percentage of patients were in the age group 51-60 comprising of 35%.…”
Section: Age Comparisonmentioning
confidence: 67%
“…In this study group of 100 patients percentage of patients >3.5 gm/dl is 72% and 26% patients had serum albumin levels of 3.5 -2.8gm/dl and 2% patients with <2.8gm/dl compared to 38% with >3.5 gm/dl and 62% with serum albumin <3.5 gm/dl In a study conducted by Vikrant M Bhagavat et al [6] on role of serum albumin and BMI as predictors of post operative morbidity and mortality in major abdominal surgeries. In study conducted by Amir Akirov et al [8] 65% patients had serum albumin level >3.5gm/dl, 29% patients had serum albumin level in between 2.5 -3.5 gm/dl and 5% patients with serum albumin level 2.5gm/dl and below.…”
Section: Serum Albumin Comparisonmentioning
confidence: 67%
See 1 more Smart Citation
“…In a similar study conducted by Bhagvat et al found that number of patients were highest (34%) in the age group 31-40 years, and the highest number of complications was noted in the age group of 51-60 years. 5 However, Kumar et al, found that the highest number of patients belonged to the age group 51-60 years of age and the maximum number of complications were also found in the same group. 6…”
Section: Discussionmentioning
confidence: 96%